The Extent of the Authoritativeness of the Source Intellect in the Exegesis of the Qur'an with Emphasis on the Interpretation of the Manahej al-Bayan - Muhammad Hadi Ghahari Kermani (آموزه‌های قرآنی, 2021)
There is disagreement among the defenders of ijtihad exegesis about the scope of the authority of reason in the exegesis of the Qur'an. For example, there is a difference between the commentators of the school of separation (Tafkik school) and their opponents in this regard. The school of separation refers to the epistemological system that insists on the separation of the Qur'an, argument and mysticism (scriptural, intellect and intuitive knowledge), and believes that these are three ways and sources of knowledge whose products have nothing to do with each other and the data of each of these knowledge sources should not be used to understand and interpret the data of the other two sources. In this article, we have explained the views of Ayatollah (Romanized: āyatollāh) Maleki Miyanaji in the exegesis (Tafsir) of Manahej al-Bayan, as one of the defenders of the school of separation (Tafkik school) in the field of the authority of the source intellect in the exegesis of revelation. First, the meaning of intellect and its types (source intellect and Mesbah intellect) became clear, and based on that, the ijtihad exegesis of the Qur'an was divided into three types: scripturalist, intellectualist and intuitionist, and considering that Mesbah intellect and intuition was specifically (particularly, particularization) out of the title of the article, so we continued the discussion on the extent of source intellect and examined the types of intellectualist (rationalist) ijtihad exegesis, namely rational axioms, intellectual proofs (rational arguments), theological, philosophical and scientific fundamentals and perceptions of practical intellect in the Manahej al-Bayan. It was concluded that, apart from philosophical and scientific principles, other types of intellectualist (rationalist) ijtihad interpretation have been proposed in the exegesis (Tafsir) of Manahj al-Bayan; Therefore, from the point of view of Ayatollah Maleki, the extent of the authority of the source intellect in the exegesis of the Qur'an includes all the mentioned types, except for philosophical and scientific fundamentals. The research method in this research is descriptive analysis.